Upaya Peningkatan Keamanan Siber Indonesia oleh Badan Siber dan Sandi Negara (BSSN) Tahun 2017-2020 - Haryanto, Agus; Sutra, Satya Muhammad (Global Political Studies Journal, 2023)
This research analyzes about the strategy carried out by the National Cyber and Crypto Agency (BSSN) as the national cybersecurity institute. In this research, the author utilizes the Theory of Securitization and The Concept of Cybersecurity. Based on the data obtained, BSSN was formed by the Presidential Regulation on BSSN which state that BSSN is tasked with implementing cybersecurity effectively and efficiently by utilizing, developing and consolidating all parties related to cybersecurity. BSSN used the Global Cybersecurity Index framework to improve the national cybersecurity capability. The GCI measures the commitment of countries in cybersecurity according to the five pillars: legal measures, technical measures, organizational measures, capacity development, and cooperative measures. The strategy of BSSN is expected to be able to face the problems and challenges in the present and future era. Keywords— Cybersecurity, Global Cybersecurity Index, Indonesia, the National Cyber and Crypto Agency